Midostaurin: a multiple tyrosine kinases inhibitor in acute myeloid leukemia and systemic mastocytosis - Schlenk, Richard Friedrich; Kayser, Sabine (Small molecules in hematology, 2018)
Midostaurin (PKC412, Rydapt®) is an oral multiple tyrosine kinase inhibitor. Main targets are the kinase domain receptor, vascular endothelial-, platelet derived-, and fibroblast growth factor receptor, stem cell factor receptor c-KIT, as well as mutated and wild-type FLT3 kinases. Midostaurin was approved by the Food and Drug Administration (FDA) and the European Medical Agency (EMA) for acute myeloid leukemia with activating FLT3 mutations in combination with intensive induction and consolidation therapy as well as aggressive systemic mastocytosis (ASM), systemic mastocytosis with associated hematological neoplasm (SM-AHN) or mast cell leukemia (MCL). Several clinical trials are active or are planned to further investigate the role of midostaurin in myeloid malignancies and mastocytosis.
Gesehen am 18.03.2020